Experimental investigation of vapour compression chiller based on transient cooling performance influenced by expansion devices - Kittiwoot Sutthivirode (Case Studies in Thermal Engineering, 2020)
This paper proposes the experimental investigation of a vapour compression refrigerator working as the water chiller (VCR-chiller) influenced by the expansion devices. The comparative cooling performance is implemented based on the transient operation (parameters of interest as a function of time). The expansion devices, thermostatic expansion valve (TEV), needle valve (NEV) and capillary tube (CT), are investigated under the same condenser, evaporator and compressor. The external performance parameters (cooling temperature, cooling load, electricity consumption, and COP) influenced by the expansion devices are assessed. The internal performance parameters (refrigerant temperature, refrigerant pressure and refrigerant mass flow rate), which indicate the flow state of the refrigerant, are also used to assess the deep impact of the expansion devices on the cooling performance. It is found that the cooling performance of VCR-chiller is strongly influenced by the expansion devices. The highest possible COP based on transient operation is achieved when using NEV while that produced by TEV is not much lower than NEV. However, using CT provides the lowest COP due to an uncontrollable refrigerant mass flow rate and its own characteristics. The findings indicate that attention must be paid to the selection of the expansion device for the VCR-chiller.